The role of Google dorking in detecting personal data leaks - Sofiia Lysiuk; Larysa Tereminko; Теремінко Лариса (II. Rákóczi Ferenc Kárpátaljai Magyar Egyetem, 2025)
Abstract. The modern digital world is developing incredibly fast, leading to the mass digitalisation of various services, communications, and information storage. However, this progress has a downside, which is the growth in cyber threats, among which personal data leaks occupy a special place. It is essential for cybersecurity specialists to be equipped with tools that enable them to detect leaks at an early stage in order to decrease damage and quickly take countermeasures. Google dorking can be helpful in this case. It is important to be aware that this tool can be used by both malicious attackers to search for vulnerabilities and security specialists to identify issues. Google dorking is simply a method of targeted analysis and highly accurate online search. It is based on using special operators and commands in the Google search system that allow you to filter results according to specific criteria. The purpose of such a search is to find information that is technically public and indexed by a search robot, but according to the plan, should be hidden from the general public. For instance, these could be temporary files, documents with incorrect access settings, or the contents of web server directories where confidential information has accidentally ended up. As a result, Google dorking is a powerful open source intelligence (OSINT) tool that reveals not only security gaps but also traces of careless data handling. The object of such searches is mostly personal data. Today, this concept covers a much wider range of information than just a name or address. Personal data includes any information relating to an identified individual. This can be identification numbers, email addresses, biometric data, location data, IP addresses, health information, financial transactions, and even cookies. The leakage of these categories of data poses the most serious risks, including fraud, identity theft, and phishing attacks, making their protection a priority.
Teljes kiadvány: https://kme.org.ua/uk/publications/rol-bezpeki-v-transkordonnomu-ta-mizhnarodnomu-spivrobitnictvi/
Keywords: Google dorking; personal data; leak